Cognitive behavioral therapies in the treatment of internet addiction - Küçükkaraca, Nilgün; Pak, Halil (Journal of Dependence, 2023)
Internet addiction carries the risk of turning into a social problem due to the increase in the relationship with the internet in everyday life during the COVID-19 pandemic. Furthermore, cognitive behavioral therapy is one of the effective practice approaches in fighting against internet addiction. On the other hand, group therapies aim to show group members that they are not alone in their problems and develop social support systems while contending with these problems. In addition, group members become role models for each other. Turkey has also risk of that internet addiction become a social problem. However, there are a few studies in Turkey, investigating the effects of cognitive behavioral therapies in the treatment of internet addiction. Therefore, the aim of this study is to discuss cognitive behavioral therapy, which is one of the intervention approaches that can be used when working with internet addiction at group level. For this purpose, in this study, the concept and diagnosis criteria of internet addiction, interventions for internet addiction, cognitive-behavioral group therapies, and cognitive behavioral group therapies in the treatment of internet addiction were addressed within the framework of empirical research in the literature. To conclude, cognitive behavioral group therapies reduce the symptoms of internet addiction. There is nonetheless a need for research regarding different age groups, women, and COVID-19 pandemics as a risk factor.
Keywords: Internet addiction; problematic internet use; cognitive behavioral therapy; cognitive behavioral group therapy